2019
DOI: 10.7249/rr4262
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the societal burden of multiple sclerosis: A study into the non-clinical impact of the disease, including changes with progression

Abstract: R® is a registered trademark.RAND Europe is a not-for-profit research organisation that helps to improve policy and decision making through research and analysis. RAND's publications do not necessarily reflect the opinions of its research clients and sponsors.All rights reserved. No part of this book may be reproduced in any form by any electronic or mechanical means (including photocopying, recording, or information storage and retrieval) without permission in writing from the sponsor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 79 publications
1
4
0
Order By: Relevance
“…The aim of this investigation was to examine the role of MS symptomatology on social integration and the subsequent role that social integration and support have on general health and PWB among individuals with MS. Consistent with previous contentions, fatigue and pain contributed to reductions in social integration (Kratz et al., 2017; Rincon et al., 2019). Results also suggested that despite the possible reduction in social integration due to MS symptomatology and other factors related to one's MS, increased engagement in healthy socialisation is in fact related to better perceived general health, physical functioning and mental health in MS.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The aim of this investigation was to examine the role of MS symptomatology on social integration and the subsequent role that social integration and support have on general health and PWB among individuals with MS. Consistent with previous contentions, fatigue and pain contributed to reductions in social integration (Kratz et al., 2017; Rincon et al., 2019). Results also suggested that despite the possible reduction in social integration due to MS symptomatology and other factors related to one's MS, increased engagement in healthy socialisation is in fact related to better perceived general health, physical functioning and mental health in MS.…”
Section: Discussionsupporting
confidence: 88%
“…In particular, one out of four individuals reported that they stopped visiting friends and family due to poor mobility. Reports of pain, fatigue, cognitive difficulties and bladder incontinence (and the uncertainty of such symptoms) have all been shown to contribute to social isolation (Kratz et al., 2017; Rincon et al., 2019). Unemployment is also a major contributing factor to loneliness.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…PwMS and fatigue particularly tend to struggle with catastrophizing and pressurizing thoughts [ 38 ], as well as worries about the future and negative feelings [ 42 ]. As these unpleasant inner experiences might be triggered in pwMS within the first chapter, they are provided with information on how to face these feelings in the chapter “dealing with emotions”.…”
Section: Overview Of the Fatigue Coursementioning
confidence: 99%